EVALUATION OF HEMODYNAMIC AND BIOMARKER CHANGES IN PATIENTS UNDERGOING SURGICAL AORTIC VALVE REPLACEMENT - Slaveski, Dimce; Lončar-Stojiljković , Dragana; Gavrilovska Brzanov , Aleksandra; Bozhinovska, Marija; Sulejmani, Haris; Jovanovski Srceva , Marija (Sanamed, 2025)
Background: Aortic stenosis (AS) is a systemic disease characterized by valvular obstruction, ventricular remodeling, and perioperative vulnerability to oxygen supply–demand imbalance. This study evaluated perioperative metabolic and biomarker dynamics and early postoperative outcomes in patients undergoing surgical aortic valve replacement (AVR).Patients and Methods: A prospective observational study was conducted on 60 consecutive adults with severe AS who underwent surgical AVR at a single center. Demographics, anthropometric data, intraoperative variables, complications, and pre- and postoperative hemodynamic and laboratory parameters were evaluated. Postoperatively, the following were assessed at 6 and 24 hours: mean arterial pressure (MAP), arterial oxygen saturation (SaO₂), partial pressure of oxygen (PaO₂), pH, partial pressure of carbon dioxide (PaCO₂), hemoglobin (Hb), lactate, and creatine kinase–MB isoenzyme (CK-MB). Continuous data are presented as mean ± standard deviation (SD) or median (interquartile range, IQR). Paired t-tests were used to compare values between 6 and 24 hours.Results: The mean age was 69.9 ± 7.3 years; 58.3% were male. Mean anesthesia and operation times were 151.5 ± 21.8 and 126.8 ± 20.6 minutes, respectively; mean cardiopulmonary bypass (CPB) and cross-clamp times were 78.3 ± 17.6 and 58.5 ± 16.7 minutes. Nearly half of the patients (46.7%) had no postoperative complications; others experienced bleeding (16.7%), arrhythmias requiring therapy (6.7%), permanent pacemaker implantation (8.3%), re-exploration (6.7%), infection (8.3%), respiratory failure (3.3%), or renal failure (3.3%). From 6 to 24 hours postoperatively, lactate decreased (2.34 ± 0.96 →1.87 ± 0.98 mmol/L; p = 0.006) and CK-MB declined (52.5 ± 34.2 →39.0 ± 30.8 U/L; p = 0.001), while Hb increased (103.5 ± 10.1 →120.1 ± 22.9 g/L; p < 0.001). pH decreased modestly (7.396 ± 0.057 →7.365 ± 0.065; p = 0.015). MAP, SaO₂, PaO₂, and PaCO₂ showed no significant changes. The median hospital stay was 7 days (IQR 6–8).Conclusions: In patients undergoing surgical AVR for AS, early postoperative trends demonstrated an improving metabolic profile (lower lactate) and biomarker normalization (CK-MB) with stable oxygenation, alongside low-to-moderate complication rates and a consistent 7-day median stay. Integrating perioperative oxygen-balance markers and cardiac biomarkers with imaging and left ventricular hypertrophy (LVH) assessment may refine timing and risk stratification for intervention. Prospective studies with standardized imaging and longer follow-up are warranted to link early metabolic recovery with ventricular remodeling and clinical outcomes.
Keywords: Aortic stenosis; aortic valve replacement; lactate; creatine kinase–MB isoenzyme; biomarkers